ANALISIS KEMAMPUAN SISWA MENYELESAIKAN SIKLUS AKUNTANSI PERUSAHAAN JASA DI SMK NEGERI 8 PALEMBANG - Nopita Nopita; Neta Dian Lestari; Nova Pratiwi (FKIP Unswagati, 2022)
AbstractAccounting is a compulsory subject given to accounting majors which contains material on the service company cycle.Â The pattern of learning which has implemented so far at SMK Negeri 8 Palembang has been optimal.Â Based on it, the problem in this study is how is the ability of students to complete the accounting cycle of service companies at SMK Negeri 8 Palembang. The purpose of this study was to determine the ability of students to complete the service company accounting cycle at SMK Negeri 8 Palembang.Â The research method that is used is descriptive statistical method. The results showed that the level of students' ability to complete the service company's accounting cycle in the cognitive domain of students' abilities